Policies, Institutions, and Markets: Stronger evidence for better decisions: January 2013 through June 2014 progress report - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2014)
Sound policies, robust institutions, and well-function-ing markets complement technological discovery in agricultural science to ensure that consumers have access to nutritious and affordable food, producers have incentives to plant and harvest, and the myriad participants in complex value chains are well linked in mutually beneficial connections. The CGIAR Research Program on Policies, Institutions, and Markets (PIM) provides foundations of anal-ysis and knowledge for food systems that help smallholder farmers and poor consumers live better lives.